Analysis of historical dark data shows multiple regime changes among pelagic migratory fishes around Japan over 120 years - Shin, Nagai; Sasai, Yoshikazu; Katsumata, Chifuyu; Nakagawa, Hiromi; Morimoto, Hiroshi (Frontiers in Marine Science, 2025)
An analysis of long-term (over-100-year) continuous catch data at local to regional scales (tens to hundreds of kilometres) is needed to deepen our understanding of the interaction between regime shifts of multiple fish species and marine environmental change. To this end, we retrieved century-scale timeseries of catches of sardines, mackerels, and horse mackerel, which are typical pelagic migratory fishes in the waters around Japan, from fishery statistical books for coastal Japanese prefectures and examined their spatiotemporal characteristics by applying a wavelet transform. We obtained the following key results: (1) Based on statistically significant wavelet power spectra of fish catches, regime shifts around Japan over the past 120 years occurred in the order of sardines (composed of Japanese sardine, Japanese anchovy, and red-eye round herring) in the 1930s, horse mackerel around 1960, mackerels in the 1970s, Japanese sardine in the 1980s, and horse mackerel in the 1990s. (2) Based on statistically significant wavelet coherences and phases between the North Pacific Index (NPI) in winter and fish catches, winter NPI was related to catches of Japanese sardine in the 1980s in the Northern Pacific (NP), Southern Pacific (SP), Central Sea of Japan (CSJ), and Southern Sea of Japan (SSJ) as well as to catches of mackerels in the CSJ and SSJ and catches of horse mackerel in the NP and SP. Despite the huge time and effort required to retrieve printed statistical books mainly held in library collections, we conclude that analogue catch data are invaluable for understanding the spatiotemporal variability of multiple fish species at 100-year scales.